Faktor-faktor Yang Mempengaruhi Perilaku Konsumsi Rumah Tangga Muslim di Perbatasan Rao Pasaman Sumatera Barat - Elmunawaroh Elmunawaroh; Asyari Asyari; Anwar Sholihin (Jurnal Ilmiah Ekonomi Islam, 2023)
Consumer behavior that is vulnerable to rapid changes because it relates to everyday life in order to meet their needs. High consumption is the result of the rapid development of society. So that culture becomes a factor causing consumption behavior. Culture is related to knowledge, beliefs, morals, and other abilities and behaviors that are obtained from society. Cultural values will have an impact on the purchasing and consumption habits of community members in marketing. Where the customer will give high value to the achievement of the goods. As a result, consumers compete to get these products, causing excessive consumption. This high lifestyle is accompanied by an era that continues to develop and is followed by an outside culture that is free and easy to enter which is able to change people's lifestyles to be a little excessive. The next factor is religiosity which is considered as a representation of a Muslim's ability to apply what he believes in and understands from the teachings of his religion in everyday life. Like things that can prevent self-harm. This study aims to determine the factors that influence the consumption behavior of Muslim households on the border of Rao Pasaman, West Sumatra. This research method is classified as a quantitative research. The data used are primary data obtained from filling out questionnaires by respondents using a Likert scale measurement. The sampling technique used in this study was purposive sampling with a population of 7,024 with a sample of 100 people. The data analysis technique used is multiple linear regression. The analysis of this study uses the SPSS application based on the results of hypothesis testing which shows that culture, lifestyle and religiosity as a whole influence consumption behavior. Culture is 2.024 with a significance of 0.046